Serum Adiponectin Levels and Changes in Glucose Metabolism before and after Treatment for Thyroid Dysfunction - Ozdemir, Didem; Usman, Aydan; Dagdelen, Selcuk (Internal Medicine, 2015)
Objective Adiponectin is an adipokine which is known to decrease in individuals associated with obesity and insulin resistance. In this study, we aimed to investigate the serum adiponectin levels and glucose metabolism in patients with thyroid dysfunction before and after treatment. Methods Newly diagnosed overt hypothyroid (n=20) and thyrotoxic (n=23) patients and healthy controls (n=20) with a body mass index of <30 kg/m2 were evaluated prospectively. Patients with a known state of insulin resistance, including prediabetes and overt diabetes, and individuals with chronic diseases were excluded. Thyroid function and fasting plasma glucose (FPG), insulin, homeostatic model assessment (HOMA) insulin resistance (HOMA-IR) and HOMA-beta cell function (HOMA-beta), lipid and adiponectin levels were investigated in the basal state and after the restoration of euthyroidism. Results The basal fasting FPG levels were lower in the hypothyroid patients than the control subjects (p=0.02) and similar between the thyrotoxic patients and control subjects (p=0.127). The basal HOMA-beta levels were higher in the patients with hypothyroidism than in those with thyrotoxicosis (p=0.015). Following the restoration of euthyroidism, the FPG levels significantly increased in the hypothyroid patients (p=0.002) and decreased in the thyrotoxic (p=0.001) patients. The basal plasma adiponectin levels were 14.55±8.4 mcg/mL, 13.79±9.13 mcg/mL and 11.68±6.0 mcg/mL in the hypothyroid and thyrotoxic patients and healthy controls, respectively (p=0.503). The adiponectin levels decreased significantly in the patients with hypothyroidism (p=0.047), whereas they did not change in the patients with thyrotoxicosis (p=0.770) after achieving euthyroidism. Conclusion In this study, following the restoration of euthyroidism, the FPG levels increased in the hypothyroidism patients and decreased in the thyrotoxicosis patients, despite the lack of changes in the HOMA-IR and HOMA-beta levels. Meanwhile, the hypothyroid, thyrotoxic and euthyroid subjects had similar basal adiponectin levels, and a significant decrease in the adiponectin levels was observed after treatment for hypothyroidism, despite the absence of changes after treatment for thyrotoxicosis, indicating the need for further studies with a larger sample size.